A 69-Year-Old Male with Right Hemiparesis, Type II Diabetes Mellitus, Uncontrolled Stage I Hypertension with Psychosocial, Cultural, Lifestyle, Low Education Level, and Low Economic Status Risk Factors - Hafidah, Qonitatun; Nurrakhma Arum Kurnia, Siti; Nur Rakhmani, Alidha (Jurnal Ilmu Kedokteran Keluarga, 2024)
This article discusses the case of a 69-year-old male with right hemiparesis, Type II Diabetes Mellitus, and uncontrolled Stage I hypertension, accompanied by multiple risk factors including psychosocial, cultural, lifestyle, low education level, and low economic status. A multidisciplinary approach was implemented to manage the patient holistically, focusing on blood sugar and blood pressure control, physical therapy for hemiparesis recovery, and family empowerment to support treatment adherence. This study highlights the importance of comprehensive interventions that address social determinants of health to improve the patient’s quality of life and reduce the risk of further complications.